PTH-117 Thymic Stromal Lymphopoietin Is Primarily Reduced In Refractory Coeliac Disease Duodenal Mucosa. (9th June 2014) - Biancheri, P; Di Sabatino, A; Fornasa, G; Papadia, C; Shidrawi, R; Woods, E; Forbes, A; Rescigno, M; Corazza, GR; MacDonald, TT
Abstract : Introduction: Thymic stromal lymphopoietin (TSLP), a cytokine released by enterocytes and gut dendritic cells, promotes the development of Foxp3+ regulatory T cells and at the same time inhibits the development of pro-inflammatory T helper (Th)1 and Th17 cells. While mucosal TSLP expression is down-regulated in untreated coeliac disease (CD), its levels are unknown in refractory CD (RCD), in which the transformation of aberrant intraepithelial T cells predisposes to the emergence of enteropathy-associated T cell lymphoma. Therefore, we evaluated the expression of TSLP and its receptor (TSLP-R) in the duodenal mucosa of patients affected by RCD. Methods: Duodenal biopsies were collected from 12 RCD patients, 16 uncomplicated CD patients before and after 12 months of gluten-free diet, and 14 control subjects. The gene expression of TSLP and TSLP-R was evaluated on biopsy homogenates by quantitative RT-PCR, and the data were normalised for cytokeratin 18 expression. The protein expression of TSLP and TSLP-R was studied on biopsy homogenates by immunoprecipitation and on biopsy sections by confocal microscopy. Results: In vivo mucosal TSLP expression was significantly reduced both at the mRNA and protein levels in the duodenum of RCD and untreated CD patients compared to treated CD patients and controls, without differences between RCD and untreated CD patients and between treated CD patients and controls. TSLP transcript down-regulation in untreated CD mucosa was confirmed after normalisation for cytokeratin 18. TSLP-R was expressed in the duodenal mucosa both at the gene and the protein level, without significant differences between RCD, untreated and treated CD patients and control subjects. Confocal microscopy analysis confirmed these findings. Conclusion: TSLP expression is primarily reduced in the duodenal mucosa of RCD patients. Further studies are needed to clarify the influence of TSLP reduction on the process of immunosurveillance in RCD. Disclosure of Interest: None Declared.